16 Comparison of Characteristics and Outcomes for Older Adults Admitted to Specialty Wards Versus Outlying Wards at Royal Bournemouth and Christchurch Hospitals. (6th February 2020) - Stafford, A; Martin, A; Tiwari, D
Abstract: Background: At Royal Bournemouth and Christchurch Hospitals (RBCH) elderly patients are admitted to either the acute medical unit or the older person's assessment unit. If the inpatient stay is likely to be longer than 72 hours, then patients are transferred to one of three elderly care wards. If these wards are at capacity, then patients must be outlied to other wards. Introduction: GMC guidance June 2014, states hospital inpatients should have a named consultant. Studies have shown that length of stay and outcomes can be affected when the patient is on an outlying ward. This issue affects many hospitals and specialties, and also impacts older frail patients at RBCH. During winter elderly care admission rates increase, and more patients are outlied. Our aim was to improve the care and outcomes for elderly care patients treated on outlying wards. Methods: The notes of 50 specialty ward patients and 50 outlying patients were compared from the first two weeks of January and February 2019 using scanned electronic records where elderly care was responsible for their treatment. We studied demographic characteristics, length of stay, mortality, readmission within 30 days of discharge, frequency of consultant review, escalation plans, discharge destination and ward moves. Interventions: A dedicated outlying team was created for the 2018/2019 winter to attempt to improve outcomes for outlying elderly care patients. This team consisted of a geriatrician, registrar, SHO and allied health care professionals including a physiotherapist and discharge coordinator. Results: Our results showed that outlying patients had a significantly longer average length of stay compared to patients on specialty ward (13.8 days vs 8.2 days, p=0.01). A significantly higher proportion of patients in outlying wards did not have a consultant review every 72 hours (66% vs 8.3% specialty ward patients, p=0.001). However the specialty ward patients had a significantly higher number of readmissions within 30 days (30.6% vs 16%, p=0.04). Conclusions: We found that despite a dedicated team, outlying patients had a significantly longer length of stay and were seen by a consultant less often than patients on a specialty ward. Further work is needed to ensure equality of care for these patients. Patients with complex medical needs are generally triaged to specialty wards, which may account for their higher readmission rate.